2022
DOI: 10.1021/acs.analchem.2c00865
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Screening of Antigen-Specific Nanobodies from Mammalian Cells Expressing the BCR Repertoire Library Using Droplet-Based Microfluidics

Abstract: Nanobodies, also known as VHHs, originate from the serum of Camelidae. Nanobodies have considerable advantages over conventional antibodies, including smaller size, more modifiable, and deeper tissue penetration, making them promising tools for immunotherapy and antibody-drug development. A high-throughput nanobody screening platform is critical to the rapid development of nanobodies. To date, droplet-based microfluidic systems have exhibited improved performance compared to the traditional phage display techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This is helpful for alpaca plasma cell enrichment during nanobody development. The proportion of plasma B cells during antigen immunization determines the effectiveness of antigen-specific antibody generation [78][79][80]. In this study, we found that the proportions of plasma B cells dramatically increased by day 17 but were significantly reduced by day 19 (day 5 after the second HA immunization), suggesting that the proportion of plasma B cells would reach a peak at three days after the second immunization.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This is helpful for alpaca plasma cell enrichment during nanobody development. The proportion of plasma B cells during antigen immunization determines the effectiveness of antigen-specific antibody generation [78][79][80]. In this study, we found that the proportions of plasma B cells dramatically increased by day 17 but were significantly reduced by day 19 (day 5 after the second HA immunization), suggesting that the proportion of plasma B cells would reach a peak at three days after the second immunization.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, we found that the proportions of plasma B cells dramatically increased by day 17 but were significantly reduced by day 19 (day 5 after the second HA immunization), suggesting that the proportion of plasma B cells would reach a peak at three days after the second immunization. Plasma cell dynamics during the specific antigen immunization should offer valuable references for nanobody discovery in immunized camelids [79,80]. However, the sampling periods between the first and second immuniza-tions were not studied here.…”
Section: Discussionmentioning
confidence: 99%
“…[4] IgG + memory B cells and plasmablasts have been stained with fluorescently labeled antibodies or fluorochrome conjugated antigens for FACS isolation, but antigen-specific plasma cells have not, given that they lack surface IgG expression. [5] New formats have extended the application scenario to phenotypic analysis of antibody secreting cells based on structured hydrogel-based microcontainers, [6,7] microwells, [8,9] or waterin-oil microdroplets [10,11] to isolate cells, accumulate secreted molecules, and perform sorting. For instance, a droplet microfluidics system CelliGO was developed for mAb discovery, where IgG activity was screened by fluorescence-based bioassays and paired antibody V genes were sequenced by barcoded reverse transcription with an in-droplet single-cell workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its merits of precision, throughput, compatibility, independence, and lack of contamination, microfluidics, especially droplet microfluidics, is becoming a powerful tool for single-cell lysis . According to the detailed principle, single-cell lysis methods based on microfluidics can be classified as physical and chemical protocols .…”
Section: Introductionmentioning
confidence: 99%